Comparative analysis of existing multi-sided digital platform initiatives - Bryan Verfaillie; Marlies Van der Wee; Sofie Verbrugge (International Telecommunications Society (ITS), 2021)
Digital platforms are omnipresent in our society. For example, streaming movies via Netflix, interacting with friends through social media, or using Deliveroo to order your meal. Digital platforms and digital marketplaces caused a big impact on the value creation process within different application domains. Actual digital ecosystems have appeared and the value propositions of traditional players within different domains got challenged by new and more integrated offers. Within this setting, also smaller-scale initiatives try to find their position. Local initiatives such as energy management platforms to link residents with (renewable) energy suppliers, or community platforms to link neighbours and city or village initiatives, especially in "online-only" times are appearing fast. Although the number of both successful and failed cases is constantly growing, systematic understanding of the reasons behind this, is still lacking. This paper wants to add to this understanding by analysing digital platform initiatives from different points of view. The overall research question tackled in this paper is to determine critical characteristics that can impact the success of the digital, multi-sided platform business model. To achieve this, a conceptual framework that allows to analyse and compare platforms is presented. The framework is then applied on different existing platform solutions, in a broad range of application domains, to identify specific design choices and compare the different platforms. Overall, more general insights in the role of network effects, pricing strategy, and other key features that impact the risk of failure, are obtained. The analyses indicate that positive network effects are predominantly present which is important for the growth of the user base. Pricing schemes indicate that general customers do not want to spend a lot of money to use a platform. Therefore, they usually can use it for free. Advertisers play a crucial role in the revenue stream for a platform but too much ads can irritate the end user. Platforms also tend to use third parties for services which reduces the time to market and lowers the investment risk. Platforms immediately benefit from other technological advantages like scalability. Due to the low homing-costs for users, there is room for competition in each domain but of course platforms try to differentiate their offer from their competitors.
Keywords: 330; Digital Platforms; Multi-Sided Platforms; Network Effects; Pricing; Multi-Homing Cost